Republic of Korea : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2001)
The paper discusses potential output, the output gap, and inflation in Korea. The paper explores the information content of potential leading indicators of inflation. A broadly balanced current account has been the suggested norm for Korea over the medium term. The challenge is to help build a more robust bond market that prices risk appropriately. The features of pension schemes in Korea and the problems they face are outlined. The paper reviews pension reform, banking sector, corporate sector, and foreign exchange crises with respect to Korea.